Pengaruh Kecukupan Modal, Risiko Pembiayaan, Efisiensi Operasional, dan Likuiditas Terhadap Profitabilitas Pada Bank Umum Syariah di Indonesia Periode 2011-2015 - Nur Rois, Dimas Ilham; , Dr. Erma Setiawati, MM.,CA (2017)
The purpose of this study was to examine and analyze the influence of Capital Adequacy, Financing Risk, Operational Efficiency and Liquidity to Profitability the Islamic Banks in Indonesia 2011-2015. The number of samples in this study is 3 Islamic Banks. Sampling techniques using a purposive sampling method. Data Analysis using multiple linear regression to test and prove the hypothesis of the study. The results showed Financing Risk and Liquidity has not effect on profitability is evidenced by the level of significance of these variables is more than 0.05. While the Capital Adequacy and Efficiency Operational significant effect on profitability because of the level of significance of these variables is less than 0.05. Keywords : Capital Adequacy, Financing Risk, Operational Efficiency, Liquidity and Profitability